2017
DOI: 10.1111/jiec.12648
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Environmental Sustainability of a Treatment Aimed at Soil Reuse in a Brownfield Regeneration Context

Abstract: A combined stabilization/solidification (S/S) and granulation treatment was shown to be effective, at lab scale, to produce secondary aggregates from a Brownfield soil slightly contaminated by metals. This treatment, as opposed to the frequently adopted "dig and dump" option, allows to combine soil management with site regeneration, minimizing landfill disposal. But is this treatment actually more environmentally sustainable than excavated soil management by dig and dump? To answer this question, we analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…). Application of experimental data as the basis for environmental assessment of waste management (Capobianco et al. ). Selection of technology data for appropriate representation of goal and scope of LCA studies (Henriksen et al. ). Quantification and communication of environmental benefits from waste prevention (Hutner et al.…”
Section: What Are the Challenges?mentioning
confidence: 99%
See 2 more Smart Citations
“…). Application of experimental data as the basis for environmental assessment of waste management (Capobianco et al. ). Selection of technology data for appropriate representation of goal and scope of LCA studies (Henriksen et al. ). Quantification and communication of environmental benefits from waste prevention (Hutner et al.…”
Section: What Are the Challenges?mentioning
confidence: 99%
“…Application of experimental data as the basis for environmental assessment of waste management (Capobianco et al. ).…”
Section: What Are the Challenges?mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Magnusson et al [3] reported that reusing excavated soil could save as much as 14 kg of carbon dioxide per ton. Additionally, Capobianco et al [4] stated that the treatment of such soils is more beneficial than digging and dumping.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies suggested alternative managing strategies for quarried soils, including using them on-site, reusing excavated materials, pre-treating before use in construction, storing them for future consideration, and using them as landfill cover applications [1,2] Furthermore, Magnusson et al [3] reported that reusing excavated soil could save as much as 14 kg of carbon dioxide per ton. Additionally, the study by Capobianco et al [4] stated that the treatment of such soils is more beneficial than digging and dumping.…”
Section: Introductionmentioning
confidence: 99%